Metacognitive and Cognitive Strategy Use in Reading Comprehension A Structural Equation Modelling Approach - Zhang, Limei (Springer Singapore, 2018)
This book examines the relationship between Chinese college-level test takers' strategy use and reading test performance using a Structural Equation Modelling Approach. With a large sample of Chinese college-level test takers, the book investigates the underlying structure of the EFL reading test. It suggests implications for classroom teachers and testing researchers about the relationship between metacognitive and cognitive strategy use in testing contexts.